2016
DOI: 10.1016/j.ecoleng.2016.06.118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small-sized crucian carp (Carassius carassius) on the growth of submerged macrophytes: Implications for shallow lake restoration

Abstract: Reestablishment of submerged macrophytes is considered important when restoring shallow eutrophic lakes. To improve water clarity and consequently the growth conditions of macrophytes, removal of plankti-benthivorous fish has been used. In subtropical shallow lakes, however, rapid recruitment of small fish, especially benthivores during restoration, may hamper early reestablishment of submerged macrophytes. Crucian carp (Carassius carassius) and Vallisneria natans are common species dominated in subtropical sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
1
15
3
Order By: Relevance
“…The major decrease in zooplankton biomass indicates that besides predating on benthic organisms ( Figure 5), crucian carp could also reduce zooplankton, potentially affecting their control of pelagic phytoplankton. Crucian carp is an omnivore, and previous gut content analyses have revealed that it may prey directly upon zooplankton, creating a community shift in dominance from large-sized cladocerans and copepods to small-sized rotifers [12]. This was exactly the pattern observed in our study (Figure 4).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The major decrease in zooplankton biomass indicates that besides predating on benthic organisms ( Figure 5), crucian carp could also reduce zooplankton, potentially affecting their control of pelagic phytoplankton. Crucian carp is an omnivore, and previous gut content analyses have revealed that it may prey directly upon zooplankton, creating a community shift in dominance from large-sized cladocerans and copepods to small-sized rotifers [12]. This was exactly the pattern observed in our study (Figure 4).…”
Section: Discussionsupporting
confidence: 88%
“…Despite the reduced top-down control of phytoplankton, water Chl-a concentrations did not increase correspondingly (Figure 3a) in these eutrophic mesocosms, in contrast to the results in similar mesocosm studies in which a clear increase in phytoplankton growth was found after introduction of crucian carp [12,15,22]. We attributed this discrepancy to the different trophic states of these mesocosm experiments.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Because they feed on at least 2 trophic levels, omnivorous fishes may affect lake ecosystems through various pathways. The presence of omnivorous fishes can increase nutrient concentrations, turbidity (total suspended solids [TSS], especially inorganic suspended solids [ISS]), and the biomass of both phytoplankton (Drenner et al 1998, Gu et al 2016, Zhang et al 2017, He et al 2019 and periphyton (Gu et al 2016), thereby suppressing the growth of submerged macrophytes (Miller andCrowl 2006, Qiu et al 2019). In a study including both the omnibenthivorous Common Carp (Cyprinus carpio Linnaeus, 1758) and the omni-planktivorous filter-feeding Silver Carp (Hypophthalmichthys molitrix Valenciennes, 1844), Zhang et al (2016) found that Common Carp substantially increased the biomass of pelagic algae but decreased the biomass of benthic algae (periphyton), whereas Silver Carp did not influence the pelagic or benthic algal biomass.…”
mentioning
confidence: 99%